2021
DOI: 10.1111/cpr.13047
|View full text |Cite
|
Sign up to set email alerts
|

CircSLC7A2 protects against osteoarthritis through inhibition of the miR‐4498/TIMP3 axis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Circular RNAs (CircRNAs), covalently closed endogenous RNAs, are noncoding RNAs characterized by a covalent loop configuration without 5′ end caps or 3′ poly(A) tails ( Ni et al, 2021 ). Furthermore, circRNAs are involved in the pathophysiological process of various diseases, such as diabetes mellitus, neurological disorders, cardiovascular diseases, skeletal muscle disease, and cancer ( Kristensen et al, 2019 ).…”
Section: The Treatments With Hif-1 In Osteoarthritismentioning
confidence: 99%
“…Circular RNAs (CircRNAs), covalently closed endogenous RNAs, are noncoding RNAs characterized by a covalent loop configuration without 5′ end caps or 3′ poly(A) tails ( Ni et al, 2021 ). Furthermore, circRNAs are involved in the pathophysiological process of various diseases, such as diabetes mellitus, neurological disorders, cardiovascular diseases, skeletal muscle disease, and cancer ( Kristensen et al, 2019 ).…”
Section: The Treatments With Hif-1 In Osteoarthritismentioning
confidence: 99%
“…A previous study showed that the RNA-binding protein FUS can affect circular RNA expression [45][46][47] . Our study could be improved by evaluating the upstream mechanisms of the circFNDC3B/miR-525-5p/HO-1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, RBPs have also been reported to participate in the splicing and formation of circRNAs. Ni and others reported that FUS binds to the GUGGU sequences at nt 358 and 409 proximal to the back-splicing sites (exon 8) and one sequence at nt 499 proximal to the back-splicing sites (exon 10) of SLC7A2 to induce circSLC7A2 formation ( Ni et al, 2021 ).…”
Section: Rna-binding Proteins In Regulating Rna Metabolismmentioning
confidence: 99%